Socio-Historical Analysis of the Cherubim and Seraphim Church Unification, Obafemi Awolowo University Campus Fellowship, Nigeria - Aluko, Oluwasegun Peter (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
Since the division of the Cherubim and Seraphim (C&S) Church in 1929, there has not been a single leader of all the factional bodies. Over the years, many attempts have been made in order to bring about a unified C&S church that would involve all the many factional bodies, which have also failed. Not until the 1980s when some group of students in higher institution came together to form a unified C&S church that will comprised of all the factional bodies. The quest for the oneness of all members of the church regardless of factions was what led to the establishment of the Cherubim and Seraphim Unification Campus Fellowship. Thus, using data collected through participant observation and secondary sources, the study focused on the beginning, growth, spread and the various practices that had led to the unification of members of the C&S Church in the higher institutions, with particular focus on the Cherubim and Seraphim Unification Church, Obafemi Awolowo University Campus Fellowship. It also assessed the impact of the unity on the fellowship and the society at large. The study found out that despite the many divisions in the C&S church at large, there is unity with regards to campus fellowships, especially the Obafemi Awolowo University Campus Fellowship from whom other branches emanated. The data collected were analysed using socio-historical and descriptive phenomenological approaches.